SOME MICROTHYRIALES AND OTHER FUNGI FROM INDONESIA - HANSFORD, C. G. (Research Center for Biology, 1954)
The species included in this paper belong mainly to the Microthyriales.New species are described in the genera: Parastigmatea Doidge (1),Hysterostomina Theiss. & Syd.(1), Aphanopeltis Syd. (1), Asterinella Theiss. (5), Asteromyxa Theiss.(1), Asterolibertia Arnaud (1),Clypeolella Hoehn.(1), Asterina Lev. (21), Lembosia Lev. (5), and Patouillardina Arnaud (1).New Combinations are made in the following genera: Chaetothyrium Speg (2),Echidnodes Theiss.& Syd.(3), Peltella Syd. (1),Trichasterina Arnaud (1), Asterolibertia Arnaud (1), and Clypeolella Hoehn. (1).